The Auto-Combustion Method Synthesized Eu2O3- ZnO Nanostructured Composites for Electronic and Photocatalytic Applications - Thekrayat H. AlAbdulaal (Materials, 2022)
An efficient and environmentally friendly combustion technique was employed to produce ZnO nanopowders with different Eu concentrations (from 0.001 g to 5 g). The structural morphology of the Eu2O3-ZnO nanocomposites was examined using XRD, SEM, and infrared spectroscopy (FT-IR). In addition, UV-Vis diffuse reflectance spectroscopy was also used to investigate the effects of europium (Eu) dopant on the optical behaviors and energy bandgaps of nano-complex oxides. The photocatalytic degradation efficiency of phenol and methylene blue was investigated using all the prepared Eu2O3-ZnO nanostructured samples. Photocatalytic effectiveness increased when europium (Eu) doping ratios increased. After adding moderate Eu, more hydroxyl radicals were generated over ZnO. The best photocatalyst for phenol degradation was 1 percent Eu2O3-ZnO, while it was 0.5 percent Eu2O3-ZnO for methylene blue solutions. The obtained Eu2O3-doped ZnO nanostructured materials are considered innovative, promising candidates for a wide range of nano-applications, including biomedical and photocatalytic degradation of organic dyes and phenol.